Mushrooms: Reservoir of vital nutrients and bioactives - Arora, Bindvi; Kamal, Shwet; Sethi, Shruti; Joshi, Alka; Sharma, V P (Mushroom Research, 2018)
Mushrooms are macro sized fruit bodies of edible fungi belonging to class Basidomycetes. These are further categorized into classes based on their utility as edible and medicinal mushrooms. Certain mushrooms are known to contain potent biomolecules of high medicinal value. Besides medicinal mushrooms, Indian population in generalpreferfive different mushrooms classified into edible category viz. button mushroom (Agaricus bisporus) preferred in northern states, oyster mushroom (Pleurotus ostreatus) which is preferred in southern states, Paddy straw mushroom (Volvariella volvacea) preferred in Orissa and neighboring states,Â  Shiitake mushroom (Lentinula edodes) and milky mushroom (Calocybe indica).Â